A gestão democrático-gerencial da educação superior: o caso da Universidade Federal de São Carlos (UFSCar) - Silveira, Ana Paula (2022)
In the mid-1960s, discussions began on the reinvention of public administration in Brazil. The administrative reinvention brought to the discussion the new models, New Public Management and Managerialism. These models were put into practice via state reforms, which occurred concomitantly with educational reforms, with the Brazilian State being a signatory to the restructuring aimed at higher education. The Federal University of São Carlos (UFSCar), created by Decree nº 3.835, of 1960, since its creation presented different administrative models, sometimes with authoritarian bias, sometimes with democratic and managerial biases. In an attempt to identify the administrative models that influenced or interconnected the administrative structuring and the elaboration of the institutional policies of UFSCar during forty years, the guiding questions of the research are: What were the institutional policies of the period from 1960 to 2010 that aligned or interconnected with the managerial approach and what were the impacts of these policies in regards to the development of UFSCar? In which moment is it possible to say that the managerial institutional policies at UFSCar began? Were there institutional policies at UFSCar that could be classified as managerial? Did these institutional policies helped discovering UFSCar's identity? In order to answer such questions, the general objective of the research were: to discuss the interface between democratic management and the specificities or tools of the Managerialism perspective in the elaboration of UFSCar's institutional policies. To carry out this research the hypothetical-deductive method was adopted as well as the following resources: bibliographic review and integrative document analysis, semi-structured interviews with “probe questions” with UFSCar managers for the production of the metatext. This metatext contains six sections: the first presents the research trajectory; the second explains the political and economic aspects that surrounded the creation of UFSCar; the third addresses the specificities of the 1980s and the need to institutionalize democracy at UFSCar and understand the university's identity; the fourth deals with the specificities of the 1990s highlighting the adoption of Situational Strategic Planning, as an administrative tool; the fifth section discusses the institutional policies designed and put into practice from 2000 to 2010 for the democratization of the access to higher education, a period in which the UFSCar Institutional Development Plan (PDI) was identified with longitudinal strategies for university management; finally, the sixth and last section presents the conclusions of this study. It can be concluded that UFSCar's institutional agents, concerned with consolidating the institution's identity as an internationally recognized university with academic and social prestige and with the use of democratic management as a guiding administrative model, constituted the UFSCar ethos emphasizing the specificities from the managerial-democratic approach which made it possible to interconnect the theoretical references of democratic management with practices and uses of managerialism for the elaboration of institutional policies while denying the centralizing authoritarian approach of the university founders.